Analisis dampak kenaikan PPN 12% terhadap perekonomian dan keuangan negara - Mufidah, Ely (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the impact of the increase in the Value Added Tax (VAT) rate to 12% on the economy and state finance in Indonesia. The method used in this research is normative, employing a legal approach to legislation and utilizing both primary and secondary legal materials, such as legal literature, academic journals, and previous research findings. The results of the study indicate that the VAT rate increase has a positive effect on state tax revenue. However, it also poses the risk of reducing people's purchasing power, which may undermine consumption. The success of this policy greatly depends on public awareness and compliance with tax obligations. Overall, the VAT rate hike needs to be accompanied by supporting policies that can strengthen consumer purchasing power and assist businesses in facing challenges. This study provides recommendations for the government to implement effective tax education and supervision measures, while also paying attention to inflationary effects to minimize the negative impact on the economy.